PEMBERDAYAAN KADER DALAM MENGENALI GANGGUAN JIWA DAN PENANGANAN KECEMASAN DI WILAYAH KERJA PUSKESMAS BABAKAN SARI BANDUNG (Poltekkes Kemenkes Bandung, 2023)
The status quo of development of science and technology has made people face various complex life changes that have led to a tendency for mental disorders. Basic Health Research (2018) confirms that the number of people with a mental health conditions in the world has reached 450 million. In Indonesia, the number of people with a mental health conditions has reached 1.7 per million to 7 per million, while in West Java, it reached 72 thousand people in 2018 (Riskesdas, 2018). The visit of patients with mental disorders is relatively high in West Java, namely the Babakan Sari Health Center, Bandung City. However, the services performed by healthcare workers are limited to inside the building. Posyandu activities by health cadres only serve toddlers and geriatric related to physical health problems. In contrast, in reality, especially with the Covid-19 outbreak, many people are experiencing mental problems, especially anxiety. Based on this, mental health services are needed in the community as a first step to be carried out by increasing the knowledge and skills of cadres about early recognition of mental disorders and handling anxiety so that it does not progress to severe mental disorders. This community service program is carried out for health cadres in the working area of ​​the Babakan Sari Health Center, Bandung City, with the output in the form of booklets and videos that cadres and families can use, as well as increased knowledge and skills of health cadres about early recognition of mental disorders and anxiety management. The method used is cadre training on early recognition of mental disorders and how to deal with anxiety. The result of this community service is an increase in the knowledge and skills of health cadres in early recognition of mental disorders and treatment of anxiety and being able to convey them to families, reducing the level of family anxiety.